EARLY GROWTH MODEL OF PELIBUEY LAMBS RAISED UNDER AN INTENSIVE PRODUCTION SYSTEM IN COLIMA, MEXICO - Macedo, Rafael; Arredondo, Victalina; Jiménez, Ana; Haubi, Carlos; Herrera, Alejandra (Chilean Journal of Agricultural & Animal Sciences, 2021)
The aim of this study was to describe the early growth of Pelibuey lambs raised under an intensive production system in Colima, Mexico, using non-linear models. Weight data were collected from 433 lambs every 30 days from birth to 180 days of age, and growth curves were estimated using non-linear and linear models. According to goodness of fit criteria, the Linear, Gompertz, Logistic and Von Bertalanffy models are suitable and show a reasonable fit for describing Pelibuey lamb’s growth, the Brody and Richards curves did not meet the convergence criterion. The parameter A denotes asymptotic weight; weight was higher in multiple born males and quadruplet born females in the Von Bertalanffy and Gompertz models, while it was also higher in males in the Logistic model. The parameter k represents maturation rate and indicates the growth speed in reaching asymptotic weight, being higher in single and twin females, and single males in all the non-linear models. From birth up to 90 days of age (weaning), weight of single lambs becomes greater than that of multiple born lambs, but from 90 days of age, weight of multiple born lambs tends to equal that of singles, which happens at 180 days of age. The early growth of Pelibuey lambs can be described with similar precision using linear and non-linear models.